AB0096 NF-KB involvement for CTLA4-IG intracellular signaling in human macrophages. (23rd January 2014) - Cutolo, M.; Montagna, P.; Soldano, S.; Sulli, A.; Seriolo, B.; Villaggio, B.; Triolo, P.F.; Felli, L.; Brizzolara, R.
Abstract : Background: Transcription factor NF-kB (nuclear factor kB) play an important role in the regulation of immune and inflammatory responses [1]. Previous studies showed that a significant downregulation of pro-inflammatory cytokine expression (TNFα, IL-1β and IL-6) was evident for cultured human macrophages treated with CTLA4-Ig fusion protein [2]. Objectives: The aim of the study was to investigate the NF-kB pathway as possible intracellular signaling target involved in the CTLA4-Ig modulation of cytokine production (TNFα, IL-1β and IL-6) in cultured human macrophages. Methods: THP1 cell line, differentiated by PMA (0.5 μg/ml for 3 hours) into adherent macrophages, were seeded in tissue culture dishes in culture medium with CTLA4-Ig [100 and 500 μg/ml for 3 and 12 hours] or without CTLA4-Ig, for mRNA extraction and qRT-PCR analysis. At the end of incubation adherent cells were harvested and mRNA was extracted and processed by qRT-PCR analysis for NF-kB1 (p50 subunit) and for TNFα, IL-1β, IL-6. Experiments were done in triplicate. Results: The qRT-PCR analysis of NFKB1 mRNA, after 3 and 12 hours from CTLA4-Ig treatment, showed a significant downregulation (p<0.001) of the gene expression vs. cnt at both concentrations [100 and 500 μg/ml]. At the same time, the qRT-PCR analysis of inflammatory cytokine mRNA, already after 3 hours from treatment, showed that CTLA4-Ig [100 μg/ml] induced a significant decrease for TNFα and IL-6 gene expression (p<0.05), compared to untreated macrophages (cnt). CTLA4-Ig [500 μg/ml] was able to reduce TNFα gene expression vs. cnt in a larger extent (p<0.001). After 12 hours from treatment with CTLA4-Ig [100, 500 μg/ml], it was still evident a significant downregulation in cytokine gene expression for IL-1β and IL-6 vs. cnt (p<0.001). Interestingly, TNFα downregulation was not still significant after 12 hours from treatment. Conclusions: The action of CTLA4-Ig may be exerted at level of the intracellular signaling (trascription factors) by downregulating NF-kB1 gene expression, together with a significant reduction in gene expression for tested inflammatory cytokines. References: Beinke S et al. Biochem J. 2004;382:393-409; 2. Cutolo M et al. Arthritis Res Ther. 2009;11(6):R176. Disclosure of Interest: None Declared